Hydrophilic porous carbon with tailored nanostructure and its sensitive hydrogen peroxide biosensor - Bao, Shu Juan (2013)
A microwave irradiation approach is used to prepare a novel hydrophilic porous carbon with a large specific surface area of 1040 m2 g−1 and uniform pore size distribution. In particular, the nanostructure can be tailored by changing microwave treatment time. As an application demonstration, the hydrophilic porous carbon is immobilized with protein haemoglobin for a hydrogen peroxide biosensor, showing higher direct electron transfer rate of haemoglobin for much higher sensitivity (0.15 mA mM−1) and lower detection limit (0.22 μM) over reported works.